Seizures Accelerate Functional Integration of Adult-Generated Granule Cells - Overstreet-Wadiche, Linda S. (J Neurosci, 2006)
In humans and experimental animals, structural and functional changes in neural circuits can accompany the development of epilepsy. In the dentate gyrus, seizures enhance adult neurogenesis, but it is unclear to what extent newborn granule cells participate in seizure-induced synaptic reorganization. During the first weeks of their existence, mouse newborn granule cells labeled with enhanced green fluorescent protein have only short dendrites that lack excitatory input. We report that pilocarpine-induced seizures accelerated the morphological development of labeled granule cells, causing their dendrites to extend through the molecular layer. In whole-cell recordings 5–16 d after seizure induction, perforant-path stimulation now evoked glutamatergic input to newborn granule cells. These synaptic responses were mediated by monosynaptic as well as recurrent polysynaptic input. Thus, seizures facilitated functional integration of adult-generated granule cells. One month later, subsequent generations of newborn cells also showed alterations in dendrite morphology, suggesting persistent effects of seizures on granule cell maturation. The sensitivity of newborn granule cells to seizures could contribute to hyperexcitability during the latent period.